Nutrient and energy intake of the 2008 world triathlon champion - Pajares, L.; Rivas, A.; Martin, T.; Moraleda, L.; Hernández, J.; Mariscal-Arcas, M. (Archivos de medicina del deporte, 2008)
The nutritional evaluation of elite sportspeople should be considered essential to achieve an optimal health status, avoiding deficiencies and covering all nutrient and energy requirements. Objective: Evaluate the diet before a competition. The performance of the sportsperson is directly related to a good diet. Material and method: We present the nutritional follow-up of the winner of the 2008 World Triathlon Championship (age=25 yrs, weight=70kg, height=179, BMI=19.55Kg/m 2) held in June in Vancouver (Canada). This follow-up gathered data for the week before the competition, using a specific Diet Register created by the research team for sportspeople resident at the CAR of Sierra Nevada, in which the daily intake of all foods was recorded. The food composition tables of the national "Alimentación y Salud" programme were used for the nutritional evaluation of reported data. SPSS 15.0 software was used for the statistical study. Results: Mean energy intake was 5370.2Kcal/day(SD: 1062.4), protein intake 219.7g/day (SD: 32.3), carbohydrates 652.0g/day (SD: 85.1) and lipids 225.2g/day (SD: 72.1) (15.1%-47.4%-37.5%). Intake of MUFA was 87.4g/day (SD:25.5), of PUFA 43.3g/day (SD: 17.8) and of SFA 45.8g/day (SD:15.2). Mean intake of vitamins with antioxidant capacity was: vit. A, 1489.8.../day (SD:629.3), vit. C 258.8 ../day (SD: 150.9) and Vit. E 22.5../ day (SD:6.8). Among minerals, mean intake of Fe was 27.6../day (SD:6.0), Zn was 24.1../day (SD:4.2) and Se was 234.9../day(SD:48.6)). Comparison of the daily energy intake (Student`s t test) showed significant differences among days (p=0.001). Conclusion: The mean energy and nutrient intakes met Spanish recommendations for the general population. We highlight differences in energy intake due to training load, with a lower intake on the first day (journey) and on the last two days before the competition. This confers special importance to the correct planning of the diet of the sportsperson during sports meetings away from home to assist an optimal performance during the competition.